1959
DOI: 10.1161/01.res.7.2.234
|View full text |Cite
|
Sign up to set email alerts
|

A Biochemical Study of Spontaneous Atherosclerosis in Pigeons

Abstract: Two breeds of pigeons (White Carneau and Silver King) have been found to have a high incidence of spontaneous atheromatous lesions in the aorta, while two breeds of homing pigeons (Racing Homers and Show Racers) seemed to be resistant to atherosclerosis. The weight of the aorta, and its cholesterol content, paralleled the severity of the disease. The levels of serum cholesterol and phospholipids, and the cholesterol: phospholipid ratio, however, appear to be unrelated to the incidence and seventy of atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1961
1961
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 8 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…2 White Carneau pigeons were chosen as the atherosclerosis-susceptible breed, Racing Homers were chosen as the resistant breed, and Autosexing Kings were chosen as a breed thought to bo genetically intermediate. The family histories of these breeds of pigeons are pertinent to this From The Vivarium and Department of Biochemistry, Bowman Gray School of Medicine, Wake Forest College, Winston-Salem, North Carolina.…”
Section: Methodsmentioning
confidence: 99%
“…2 White Carneau pigeons were chosen as the atherosclerosis-susceptible breed, Racing Homers were chosen as the resistant breed, and Autosexing Kings were chosen as a breed thought to bo genetically intermediate. The family histories of these breeds of pigeons are pertinent to this From The Vivarium and Department of Biochemistry, Bowman Gray School of Medicine, Wake Forest College, Winston-Salem, North Carolina.…”
Section: Methodsmentioning
confidence: 99%
“…Although no sex difference has been reported in the development of the naturally occurring or cholesterolaggravated disease in WC pigeons, 6 -7 the development of lesions in males and females may result from the interaction of different factors. The administration of BaP alters or provides another factor in females compared with males.…”
Section: Discussionmentioning
confidence: 98%
“…Differences between breeds in the susceptibility to the development of atherosclerosis cannot be explained by differences in known risk factors, including plasma cholesterol levels, lipoprotein distribution, or blood pressure. 6 In addition, the SR pigeon maintains its relative resistance to atherosclerosis compared with the WC pigeon even when the former is fed levels of cholesterol that are sufficiently large to cause radical yet similar changes in the physiochemical nature of lipoproteins in both strains of birds. 7 - 8 However, as with naturally occurring atherosclerosis, no difference in known risk factors could explain the breed differences in susceptibility to the disease in cholesterol-fed pigeons.…”
mentioning
confidence: 99%
“…Finally, the pellet was resuspended in complete medium and filtered through a nucleopore membrane (10 ,gm), and the cells were seeded into 100-mmdiameter dishes. Cells grew within [36][37][38][39][40][41][42][43][44][45][46][47][48] Figure 2). One-way ANOVA showed a significant difference in ACE activity between the two vessel regions (p<0.001, Table 1).…”
Section: Endothelial and Vascular Smooth Muscle Cell Culturesmentioning
confidence: 99%
“…Intrinsically defined different properties of the smooth muscle cells might have important consequences: in the best-studied avian model of atherosclerosis, the White Carneau pigeon, the neural crest-derived vessels are the least susceptible to develop the disease, the mesenchyme-derived vessels are more susceptible, and the most susceptible regions coincide with sites identified as neural crest-mesenchyme interfaces. [40][41][42] In summary, we have demonstrated that the ACEmodulatory properties of smooth muscle vary with its ontogeny. Origin-independent factors related to the anatomic location of the vessel, e.g., shear stress,43 also influence tissue ACE activity directly, suggesting that the regulation of vascular ACE activity in vivo may result from a combination of intrinsic and extrinsic factors.…”
Section: Endothelial and Vascular Smooth Muscle Cell Culturesmentioning
confidence: 99%